2010
DOI: 10.2478/v10182-010-0003-y
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of RAPD and AFLP Markers for Determining Genetic Similarity in Rye (Secale L.) Species and Subspecies

Abstract: In this work we searched for genetic similarities in twelve wild rye species and subspecies and a control (S. cereale ssp. cereale, cv. Walet), using RAPD and AFLP markers. AFLP is useful for distinguishing homo-and heterozygotes but is not recommended for evaluation of codominant markers. We assessed the usefulness of the applied methods for examining genetic similarity in rye. RAPD yielded four groups of genetic similarity, with similarity values between 0.32 and 0.81. AFLP markers distinguished two groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Lefort-Buson et al (1987) and Ali et al (1995) observed in B. napus, andFalk et al (1994) in B. rapa, that using morphological markers and geographic origin caused an increase in heterosis with increasing parental distance. Moreover, in many crops molecular DNA markers have proven to be an excellent tool for the assessment of genetic relationships to monitor genetic diversity or similarity and relatedness among breeding material (Stępień et al, 2007;Chen et al, 2008;Ćwiklińska et al, 2010;Bus et al, 2011). Relationships between the genetic distance or similarity of parental lines of F 1 hybrids with yielding ability and heterosis effect have been examined intensively for different crops, such as maize (Zea mays L.), rice (Oryza sativa L.), wheat (Triticum aestivum L.), and oilseed rape (Zhao et al, 1999;Corbellini et al, 2002;Schrag et al, 2009;Girke et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Lefort-Buson et al (1987) and Ali et al (1995) observed in B. napus, andFalk et al (1994) in B. rapa, that using morphological markers and geographic origin caused an increase in heterosis with increasing parental distance. Moreover, in many crops molecular DNA markers have proven to be an excellent tool for the assessment of genetic relationships to monitor genetic diversity or similarity and relatedness among breeding material (Stępień et al, 2007;Chen et al, 2008;Ćwiklińska et al, 2010;Bus et al, 2011). Relationships between the genetic distance or similarity of parental lines of F 1 hybrids with yielding ability and heterosis effect have been examined intensively for different crops, such as maize (Zea mays L.), rice (Oryza sativa L.), wheat (Triticum aestivum L.), and oilseed rape (Zhao et al, 1999;Corbellini et al, 2002;Schrag et al, 2009;Girke et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…primer hybridization sites, screening methods, i.e. RAPD (Ćwiklińska et al, 2010; and c -groups of similarity 1 -Ot0-6; 2 -bulk -RILs tolerant to nutrient deprivation; 3 -F 1 (Ot0-6 × Ot1-3); 4 -bulkRILs susceptible to nutrient deprivation; 5 -Ot1-3 Fig. 4.…”
Section: Discussionmentioning
confidence: 99%
“…Amplification is performed within new microsatellite and inter-microsatellite DNA regions, which are not amplified separately using RAPD (Ćwiklińska et al, 2010;Myśków et al, 2001) or ISSR (Bolibok et al, 2006;Ye et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Isozymes, RAPD and AFLP markers have been used to estimate genetic diversity/similarity in various crop species (Foisset et al, 1996;Corbellini et al, 2002) and species of the genus Brassica (Snowdon and Friedt, 2004;Hu et al, 2007). The RAPD method is one of the simplest and cheapest molecular techniques; RAPD markers have been used successfully to analyze genetic diversity, identify, quantify and characterize genetic variation in all available germplasm resources (Ćwiklińska et al, 2010;Bocianowski and Seidler-Łożykowska, 2012). The AFLP method has been applied in research involving, for example, identification of sequence variability (Vos et al, 1995) and prediction of hybrid performance in maize using AFLP and SSR molecular markers (Schrag et al, 2010).…”
Section: Discussionmentioning
confidence: 99%